Development of distribution model of passenger transportation volumes among suburban transport modes - Григорова, Тетяна Михайлівна; Давидич, Юрий Александрович; Доля, Віктор Костянтинович (Eastern-European Journal of Enterprise Technologies, 2015)
The analysis of the factors influencing the passenger traffic formation was performed. It was found that the passenger traffic formation is a complex process which is based on the route selection by passengers. The passengers’ choice is significantly affected by the availability of alternative transport modes. The technique of carrying out a full-scale survey of the passenger transportation parameters in various traffic directions of suburban passenger transport was given. A statistical analysis of changes in the share of passengers who prefer road transport of the total transportation volume on suburban routes was conducted. The influence of the ratio of traffic speeds, tariffs per kilometer of travel, capacity utilization rates, waiting time on road and rail transport modes was determined. Regression model of changes in the share of passengers who prefer road transport of the total transportation volume on suburban routes was designed. The evaluation of the statistical significance of the model was performed and conclusion on the admissibility of its use in solving the problems of optimizing the passenger transportation parameters on suburban routes was made.